2019
DOI: 10.5334/aogh.2352
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Noise-Induced Hearing Loss among Textile Industry Workers in Dar es Salaam, Tanzania

Abstract: Background: Noise-induced hearing loss (NIHL) is the most common preventable cause of deafness. The degree of NIHL is determined by intensity, duration of exposure, spectral characteristics of the noise, and individual susceptibility. Industrial workers in both developed and developing countries are all at risk of suffering from NIHL. Methods: An industry-based descriptive cross-sectional study was conducted. Data was collected using structured questionnaires, where sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
1
13
2
3
Order By: Relevance
“…The evidence at hand shows that migrant workers in Kuwait suffer from ONIHL with a prevalence of 20.4%, which is in line with the results of [ 20 , 32 ] at 21.5% in Ghana and 22.1% in Germany, respectively. However, the estimated prevalence in the present study is lower than those of [ 33 , 34 ], at 58.5% among textile workers in Tanzania and 44% among woodworkers in Nepal, respectively. Prevalence ratios can vary depending on the study sample and the nature of the workplace; therefore, they are not readily generalizable nor easily comparable.…”
Section: Discussioncontrasting
confidence: 86%
“…The evidence at hand shows that migrant workers in Kuwait suffer from ONIHL with a prevalence of 20.4%, which is in line with the results of [ 20 , 32 ] at 21.5% in Ghana and 22.1% in Germany, respectively. However, the estimated prevalence in the present study is lower than those of [ 33 , 34 ], at 58.5% among textile workers in Tanzania and 44% among woodworkers in Nepal, respectively. Prevalence ratios can vary depending on the study sample and the nature of the workplace; therefore, they are not readily generalizable nor easily comparable.…”
Section: Discussioncontrasting
confidence: 86%
“…This prevalence rate was three times higher than WHO data in 2015. A study on workers in Tanzania has found that as many as 58.5% of the total 265 workers experienced NIHL and the prevalence in men (67.7%) was higher than in women (Abraham et al 2019). A study in America stated that one of four (24%) of adults experienced hearing loss due to noise and its prevalence was more in men (Carroll et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These studies include the one conducted in Tanzania among miners where the prevalence of ONIHL was 47% with the youngest age group of 20-29 years being most affected (Musiba, 2015). In another study among textile workers in Tanzania, the prevalence of NIHL was found to be 58.8% (Abraham, Massawe, Ntunaguzi, Kahinga, & Mawala, 2019). A cross-sectional study among Tanzanian steel workers revealed a prevalence of ONIHL of 48% (Nyarubeli, Tungu, Moen, & Bratveit, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%